Proposal: A Policy on Intellectual Property for The University of the West Indies - The University of the West Indies, Office of Planning (Office of Planning, UWI, 1996)
The Office of Planning and Development proposes the adoption by the University of a policy on intellectual property which would govern the ownership and disposition of rights in intellectual products generated in the University.
Keywords: Intellectual property